2021
DOI: 10.26740/paramasastra.v8n1.p75-94
|View full text |Cite
|
Sign up to set email alerts
|

Students Willingness to Communicate Using English: A Survey Study

Abstract: In Indonesia, one of the common problems encountered by many English teachers during the process of teaching and learning in the classroom is students unwillingness to communicate using English. Having learners who are willing to communicate using English in class is essential in a language classroom that following the communicative approach (Riasati, 2012). This study aims to investigate students perceptions towards willingness to communicate using English in the classroom. It employs a quantitative approach,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 4 publications
0
10
2
Order By: Relevance
“…In contrast to the result obtained in this study, Rihardini, Yaniafari, and Mukminatien (2021), who conducted a study at SMA Negeri 12 Pekan Baru, found that the students at SMA Negeri 12 Pekan Baru have low WTC. According to 2022.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to the result obtained in this study, Rihardini, Yaniafari, and Mukminatien (2021), who conducted a study at SMA Negeri 12 Pekan Baru, found that the students at SMA Negeri 12 Pekan Baru have low WTC. According to 2022.…”
Section: Discussioncontrasting
confidence: 99%
“…The respondents of this study were 95 students of grades 10, 11, and 12 of a private high school in North Sulawesi enrolled in the first semester of the 2022-2023 academic year. The instruments used in collecting the data were a questionnaire adapted from Park and Lee (as cited in Ningsi, 2020) and a questionnaire adapted from Rihardini, Yaniafari, and Mukminatien (2021) originally from Horwitz, Horwitz, and Cope (1986). To find out the levels of students' self-confidence and their WTC in English, the MEAN score was used.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations